PENELITIAN PELESTARIAN DAN PEMANFAATAN SUMBERDAYA ARKEOLOGI - Hidayat, Muhammad (Berkala Arkeologi, 1997)
In the development that is being intensively carried out in Indonesia today, there are often conflicts of interest between sectors. Sectors that do not produce goods or services are often defeated in these conflicts. In such cases, many issues of preservation of archaeological resources are threatened. In fact, the problem of conflict that can threaten the preservation of archaeological resources will not occur if coordination, integration and synchronization between sectors are carried out optimally in programming. In addition, it is also felt that there is a lack of understanding of the legal aspects that govern matters of interest between sectors.